Глаз Лобенгулы: [роман] / А. Г. Косарев - Косарев Александр Григорьевич (Военные приключения, 2010)
Экземпляры: аб. (2020) / Инвентарный номер: 55973 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 71 / ББК: 84(2=411.2)6